KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Rachmat Aprianto; Dista Amalia Arifah (Jurnal Ekonomi dan Bisnis, 2014)
This study aims to analyze companies value on manufacture companies which is listed in Indonesian Stock Exchange from 2008 until 2010. There are many factors which influenced companies value like investment decisions, funding decisions, dividend policy, structure ownership (managerial and institusional). The population included in manufacture companies for four years. Sampling using a purposive sampling method and obtained 128 samples that meet the criteria and free from outliers. The data was analyzed by multiple regression. The results showed investment decisions, funding decisions, institusional ownership structure and significant positive effect on firm value. But for the dividend policy, structure of managerial ownership has negative effect and not significant on firm value.Keywords : investment decisions, funding decisions, dividend policy, structure ownership, firm value.